Trends in active surveillance for very low‐risk prostate cancer: do guidelines influence modern practice? - Parikh, Rahul R. (Cancer Med, 2017)
As recommended by current NCCN guidelines, patients with very low‐risk prostate cancer may be treated with active surveillance (AS), but this may be underutilized. Using the National Cancer Database (NCDB), we identified men (2010–2013) with biopsy‐proven, very low‐risk prostate cancer that met AS criteria as suggested by Epstein (stage ≤ T1c; Gleason score (GS) ≤ 6; PSA < 10; and ≤2 [or <33%] positive biopsy cores) and aged ≤76, and low comorbidity index (Charlson‐Deyo score = 0). For those patients meeting this criteria, we performed generalized estimation equation (GEE) method with incorporation of correlation in patients clustered within facility to determine the likelihood of undergoing AS. Among the 448 773 patients in the NCDB with low‐risk prostate cancer, 40 839 patients met the inclusion criteria. AS was utilized in 5798 patients (14.2%), while within the very low‐risk patients receiving treatment, up to 52.2% received radical prostatectomy. In univariate analyses, AS utilization was associated with older age, uninsured status (compared to private insurance), farther distance from facility, academic/research institutions and particularly in the New England region (all P < 0.01). After adjustments of other predictors in multivariate analysis, patients preferentially received AS if they were older (all OR's > 1 compared to younger groups), uninsured (vs. any insurance type, OR's > 1); or treated at academic/research center (OR > 1). The overall use of AS increased from 11.6% (2010) to 27.3% (2013). We found a low, but rising rate of AS in a nationally representative group of very low‐risk prostate cancer patients. Disparities in the use of AS may be targeted to improve adherence to national guidelines.